IDENTIFIKASI DEKSAMETASON PADA JAMU PENGGEMUK BADAN YANG DIJUAL DI E-MARKETPLACE SHOPEE MENGGUNAKAN KROMATOGRAFI LAPIS TIPIS - Sri Widia Ningsih; Lerny Serena Sirait; Dewi Setiyawati (JURNAL KIMIA MULAWARMAN, 2021)
The regulation of Indonesian Health Ministry number 007 of 2012 about traditional medicines registration explained that traditional medicines are prohibited from containing Drug Chemicals (DC). The aim of the study was to identify the DC of dexamethasone in Agency Fattening Herbs sold in Shopee e-marketplace. Dexamethasone is a corticosteroid drug used as an anti-inflammatory agent. Long-term use can cause a hormonal effect, iatrogenic chusing syndrome. This study was a qualitative descriptive using thin layer chromatography (TLC). The mobile phase used to identify dexamethasone in this study was Ethyl acetate: Toluen: Methanol (45 : 54: 1) and the solvent used was Chloroform: Methanol (9 : 1). Many of the samples tested were 3, namely X, Y and Z. The results of TLC formed purple stain spots on all three samples that were parallel to the comparison on 254 nm UV light. The price of dexamethasone comparison Rf is 0.53. The Rf value of the sample X was 0.34. The Rf value of sample Z is 0.53. The calculation results of Rf value were analyzed by SPSS with a significant value (p ≤ 0.001). The analysis was continued by the Duncan test to show groups that had differences. Of the three samples Agency Fattening Herbs tested two of them (X and Z) containing Dexamethasone whereas one (Y) does not has Dexamethasone. Keywords: Agency fattening herbs, dexamethasone, e-marketplace, thin layer chromatography